Evaluation of Phytochemical Contents and their Antioxidant Properties of Sunflower (Helianthus Annuuas L.) Seeds Collected from Noakhali, Bangladesh (Journal of Current and Advance Medical Research, 2025)
Background: Despite the fact that hydrogen peroxide (H2O2) is proactive, it turns to the severely reactive species and harmful hydroxyl radical (HO*) to the cell, which is then enable to interfere with pairs of nucleotides in DNA as well as, the similar way, trigger breakage of the strand due to genotoxicity (carcinogenesis, mutagenesis) and produce reactive oxygen species (ROS). Overproduction of these ROS in the cell leads to various types of chronic degenerative disorders like different types of diabetes, neurodegenerative disease, several types of cancer and so one. Phytochemicals as well as antioxidants perform a crucial task in the prevention of ROS production, which is undergo oxidative stress. However, the potential antioxidant capacity of a molecule is determined by the H2O2 scavenging rate. The hydrogen peroxide (H2O2) scavenging assay was incorporated utilizing the replacement titration assay and a UV-VIS spectrophotometer.Objective: The focus of this investigation was to determine the antioxidant potency of sunflower seeds (Helianthus annuuas L.) extracts by using H2O2 and DPPH scavenging assays, as well as polyphenol, flavonoid, and tannin contents.Methodology: We have also studied the water and ethanolic exudates of various sorts of sunflower from the Noakhali region of Bangladesh to check their polyphenol, flavonoid, and tannin residues. The antioxidant potency was also assessed applying the 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical reducing capacity.Results: The ethanolic extract of sunflower included the maximum amount of polyphenols (8.61%), flavonoids (30.67%) as well as obtained in max yields (10.15%). The solution of ethanolic exudate had upmost antioxidant characteristics in both H2O2 and DPPH radical-scavenging activity than those in the aqueous extract. The scavenging rate of DPPH and H2O2 was brought about in a dose-dependent way.Conclusion: Overall, the sunflowers examined in this present study are reliable origin of natural antioxidants that confer unique defensive mechanism adverse to free radical toxicity, are accessible sources of natural antioxidants, also can be used as a potent diet supplement or in the medicinal value against diseases.Journal of Current and Advance Medical Research, January 2024;11(1):8-16